Biomechanics of shod and barefoot running: A literature review Biomecânica da corrida com calçado e descalço: Revisão da literatura Biomecánica de la carrera con calzado y descalzo: Revisón de la literatura - Jahn V.D.S.* (2020)
© 2020, Redprint Editora Ltda. All rights reserved.This study aims to analyze and summarize the biomechanical (kinematics, kinetics and neuromuscular) differences between shod and barefoot running, through a literature review. Searches were conducted for complete articles published between 2013 and November 2018 in the Web of Science, PubMed, Scopus and SPORTdiscus databases. The search terms used were Biomechanics, Kinetics, Kinematics, Electromyo-graphy, “Surface Electromyography”; and Unshod, Barefoot, Barefeet and Running. The search resulted in 687 articles; after excluding duplicates and selecting by title, abstract and full text, 40 articles were included in the review. The results show that there are important differences in the biomechanics of running when shod or barefoot. In general, studies indicate that in barefoot running: a) individuals present forefoot or midfoot foot strike patterns, while in shod running the typical pattern is the rearfoot strike; (b) greater cadence and shorter stride length are observed; and (c) there is greater knee flexion, lower peak vertical ground reaction force and greater activation of the medial gastrocnemius. In addition, barefoot runners contact the ground with greater plantar flexion, possibly as a strategy to reduce impact when stepping without footwear. These differences, as well as runners’ individual characteristics, should be considered in the prescription of the barefoot running, in order to minimize injuries resulting from the practice. Level of Evidence II; Review.